Arf1 regulates the ER–mitochondria encounter structure (ERMES) in a reactive oxygen species‐dependent manner. (16th April 2018) - Zhang, Bing; Yu, Qilin; Huo, Da; Li, Jianrong; Liang, Chao; Li, Hongyue; Yi, Xiao; Xiao, Chenpeng; Zhang, Dan; Li, Mingchun
Abstract : The Arf family of small GTP‐binding and ‐hydrolyzing proteins are some of the most important intracellular regulators of membrane dynamics. In this study, we identified the Golgi‐localized Arf family G protein Arf1 in Candida albicans and confirmed its conserved function in regulating the secretory pathway. Interestingly, deletion of ARF1 resulted in intracellular reactive oxygen species (ROS) accumulation, and induced formation of the endoplasmic reticulum (ER)–mitochondria encounter structure (ERMES). Moreover, N ‐acetylcysteine‐mediated ROS scavenging in the arf1 Δ/Δ strain attenuated ERMES formation, indicating that intracellular ROS accumulation resulting from ARF1 deletion facilitated ERMES formation. In addition, Arf1 regulated many key physiological processes in C. albicans, including cell cycle progression, morphogenesis and virulence. This study uncovers a role for Arf family G proteins in regulating ERMES formation and sheds new light on the crucial contribution of ROS to membrane dynamics. Abstract : The Arf family of small GTP‐binding and ‐hydrolyzing proteins is one of the most important intracellular regulators of membrane dynamics. This study identified the Golgi‐localized Arf family G protein Arf1 in Candida albicans and showed that ARF1 deletion results in a ROS burst and formation of the ER–mitochondria encounter structure (ERMES).